DEVELOPMENT AND CHARACTERIZATION OF A SENSOR BASED ON CARBON NANOFIBERS: APPLICATION TO ACETAZOLAMIDE DETERMINATION IN PHARMACEUTICALS AND BIOLOGICAL FLUIDS - Mundaca-Uribe, Rodolfo; De Diego, Marta; Henríquez-Aedo, Karem; Aranda, Mario; Peña-Farfal, Carlos (Journal of the Chilean Chemical Society, 2019)
Acetazolamide (ACZ) is a carbonic anhydrase inhibitor that exhibits diuretic activity. In medicine, it is principally used in open-angle glaucoma, for prevention or amelioration of symptoms associated with acute high-altitude sickness and as an adjunct to other anticonvulsants in centrencephalic epilepsies. Furthermore, ACZ is sometimes used by athletes to mask the presence of doping substances, so its use has been banned in competitions. The aim of this work was the development of a sensor to determine ACZ in pharmaceuticals, as quality control way, and serum, for clinical and doping analyzes. The sensor has been developed modifying a glassy carbon electrode with carbon nanofibers. The electrochemical characterization of the sensor was performed by cyclic voltammetry using the redox mediator potassium ferrocyanide. ACZ electrochemical behavior was studied as well. Measurements were performed in a conventional three electrodes cell using differential pulse voltammetry. The influence of some experimental variables involved in the preparation and performance of the sensor –amount of modifier, supporting electrolyte, pH, scan rate and pulse amplitude– were optimized. This methodology provided a linear calibration plot for ACZ in the 1 – 17 μM concentration range. Furthermore, the proposed sensor exhibited suitable analytical properties, with detection and quantification limits of 0.06 μM and 0.2 μM respectively; analytical sensitivity of 1.142 μA/μM, repeatability of 0.72 %, and it was applied to determine ACZ in pharmaceuticals (tablets) and spiked human serum, being an excellent tool to perform quality control and antidoping control.